2011
DOI: 10.5194/bgd-8-9165-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-lethal effects of ocean acidification on two symbiont-bearing benthic foraminiferal species

Abstract: We conducted experiments to assess the effect of elevated atmospheric carbon dioxide concentrations on survival, fitness, shell microfabric and growth of two species of symbiont-bearing coral-reef benthic foraminifera, using <i>p</i>CO<sub>2</sub> Ievels similar to those likely to occur in shallow marine pore waters in the decades ahead. Foraminifera were cultured at constant temperature and controlled <i>p</i>CO<sub>2</sub> (385 ppmv, 1000 ppmv, and 2000 ppmv) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 76 publications
2
12
0
Order By: Relevance
“…The lower pH did not significantly affect the survival rate in agglutinated and tectinous benthic foraminifera but negatively impacted the survival rate in calcareous foraminifera (Bernhard et al, 2009a). The present study recorded noticeable mortality rates in all the three species with decreasing pH, similarly to the previous work of, Mclntyre Wressing et al (2011) who have reported that higher CO 2 concentration affects survival rate in Amphistegina gibbosa .…”
Section: Discussionsupporting
confidence: 92%
“…The lower pH did not significantly affect the survival rate in agglutinated and tectinous benthic foraminifera but negatively impacted the survival rate in calcareous foraminifera (Bernhard et al, 2009a). The present study recorded noticeable mortality rates in all the three species with decreasing pH, similarly to the previous work of, Mclntyre Wressing et al (2011) who have reported that higher CO 2 concentration affects survival rate in Amphistegina gibbosa .…”
Section: Discussionsupporting
confidence: 92%
“…This is represented in the literature showing unaffected or increased calcification rates in hyaline (low Mg-calcite: less soluble) and decreased rates in miliolid (high Mg-calcite: more soluble) species in response to elevated pCO 2 [70], [73], [76], [77]. These taxa specific differences are in line with previous studies on foraminiferal DIC uptake mechanism, showing almost linear increases in miliolid Amphisorus hemprichii and almost no change in Amphistegina lobifera in response to increasing DIC (and CO 3 2− ) concentrations in the OA range between 2 and 3 mM ([84], also discussed in [76]).…”
Section: Discussionmentioning
confidence: 93%
“…While most laboratory studies investigating calcification in symbiont-free foraminifera showed decreases in calcification rate [72], [74], [75], [82] larger photosymbiotic foraminifera show more variable responses [50], [70], [76], [77]. Also, experiments conducted under low and stagnant flow conditions exhibit mostly decreases in calcification rate [70], [72][75], [82], while experiments applying higher rates of turbulent mixing show variable responses on rates of calcification, net photosynthesis and respiration ([50], [76], [77], this study). Thus calcification responses seem to correlate to some extend with the experimental flow conditions as suggested for corals (reviewed in [83]).…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, the fitness and survival of the symbiontbearing benthic foraminifera Amphistegina gibbosa and Archaias angulatus were not directly affected by elevated pCO 2 up to 2000 µatm (McIntyre-Wressnig et al, 2011). But it is important to note that during the whole six week incubation time, calc was supersaturated ranging from 5.4 to 1.5.…”
Section: Response Of Living Calcareous Foraminifera To Undersaturatedmentioning
confidence: 94%
“…Seawater pH NBS , pCO 2 and omega for calcite ( calc ) were calculated by using the CO2Sys-program developed by Lewis and Wallace (1998) (Tables 2 and 3). Dissociation constants K 1 and K 2 were chosen according to Mehrbach et al (1973) as refitted by Dickson and Millero (1987) and the KHSO 4 dissociation constant after Dickson (1990).…”
Section: Carbonate Chemistrymentioning
confidence: 99%